The Role of Loneliness and Automatic Thoughts in Predicting Psychological Symptoms of the Individuals on Probation for Substance Use Background - Gamsız, Özge; Aypay, Ayşe (Addicta: The Turkish Journal on Addictions, 2018)
This study has sought to examine the role of loneliness and automatic thoughts of individuals on probation who have a history of substance in predicting the psychological symptoms. Following a correlational model, this study took the variables of loneliness and automatic thoughts as independent variables and psychological symptoms (i.e., anxiety, depression, negative self, somatization, and hostility) as dependent variables. The study’s working group consisted of 323 male adult individuals of at least 18 years of age who were on probation in Eskisehir’s Probation Office in Turkey. While the UCLA Loneliness Scale, the Automatic Thoughts Scale, and the Brief Symptom Inventory were used to as data collection tools, the data were statistically analyzed using Multi-Linear Regression. The results of the study reveal that loneliness and automatic thoughts together significantly predict anxiety, depression, negative self, and somatization. In regard to hostility, however, the results of the multiple regression analysis found that only automatic thoughts, and not loneliness, was a significant predictor. Citation: Gamsız, Ö., & Aypay, A. (2018). The role of loneliness and automatic thoughts in predicting psychological symptoms of the individuals on probation for substance use background. Addicta: The Turkish Journal on Addictions, 765‒788. http://dx.doi.org/10.15805/addicta.2018.5.4.0043